A Cochrane Handbook of Alcohol and Drug Misuse : a Cochrane Handbook. - Abraha, Iosief (Wiley, 2012)
Addiction to drugs and alcohol is an increasing problem that all clinicians have to deal with. This Cochrane Handbook of Alcohol and Drug Misuse serves as a concise guide to the evidence base for relevant interventions, highlighting the key points of Cochrane reviews for the busy practitioner. It covers a wide range of pharmacological and psychosocial treatments for opioid, alcohol, cocaine and other stimulant and drug misuse, offering comprehensive coverage of interventions for drug and alcohol addiction.